The Influence of Webstore Visual Design and Emotional Value on Muslimah Clothing Online Purchasing Decisions in Gen Z - Rika Sari; Eggy Armand Ramdani; Haqibul Mujib (Journal of Islamic Economics and Business, 2023)
This study aims to examine the influence of Webstore Visual Design and Emotional Value on Muslimah Clothing Online Purchase Decisions for Generation Z FEBI IAI Darussalam Ciamis students. The growing phenomenon of online business, especially among generation Z who are skilled in technology and often shop online, encourages entrepreneurs to create webstores that attract attention and can influence their buying decisions, especially in Muslim clothing. This study discusses the influence of visual webstore design and emotional value partially or simultaneously on online purchasing decisions for Muslim women's clothing in Generation Z. The uniqueness of this research lies in its deep focus on the effectiveness of the webstore design itself and its relationship with emotional value, which has rarely been studied before. The research method used a quantitative approach with the help of SPSS to analyze data from 61 respondents who were FEBI IAI Darussalam Ciamis students from generation Z. The results showed that partially, the webstore's visual design and emotional value had no significant effect on the online buying decision for Muslimah clothing in Generation Z. However, simultaneously, these two variables had a positive effect on purchasing decisions for FEBI IAI Darussalam Ciamis students. In conclusion, professionalism, honesty, transparency, and trust in webstore design contribute to consumer buying interest and create positive emotional value as a form of appreciation for the satisfaction and convenience of using the webstore, which ultimately increases the decision to purchase Muslimah fashion products online in Generation Z.